2021
DOI: 10.1136/rmdopen-2021-002008
|View full text |Cite
|
Sign up to set email alerts
|

Humoral protection to SARS-CoV2 declines faster in patients on TNF alpha blocking therapies

Abstract: BackgroundThe persistence of the SARS-CoV2 pandemic, partly due to the appearance of highly infectious variants, has made booster vaccinations necessary for vulnerable groups. Questions remain as to which cohorts require SARS-CoV2 boosters. However, there is a critical lack of data on the dynamics of vaccine responses in patients with chronic inflammatory diseases (CID) undergoing immunosuppressive/disease modifying anti-rheumatic (DMARD) treatment. Here, we present the first data regarding the decline of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
30
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(66 citation statements)
references
References 6 publications
10
30
1
4
Order By: Relevance
“…Our data are consistent with recent data suggesting reduced vaccine efficacy against Omicron infection in immunocompromised patients (14). The observed waning of antibody responses to mRNA vaccines in anti-TNF patients are in agreement with a recent small study from Geissen et al (13) who showed decreased responses and waning immunity with anti-TNF agents in 23 IMID patients at 6 months post dose 2, and also confirmed with a larger cohort in a recent pre-print (19). We also observed that IMID patients overall showed more substantial waning of both antibody and T cell responses compared to healthy controls.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Our data are consistent with recent data suggesting reduced vaccine efficacy against Omicron infection in immunocompromised patients (14). The observed waning of antibody responses to mRNA vaccines in anti-TNF patients are in agreement with a recent small study from Geissen et al (13) who showed decreased responses and waning immunity with anti-TNF agents in 23 IMID patients at 6 months post dose 2, and also confirmed with a larger cohort in a recent pre-print (19). We also observed that IMID patients overall showed more substantial waning of both antibody and T cell responses compared to healthy controls.…”
Section: Discussionsupporting
confidence: 94%
“…Although many IMID patients mount adequate serological responses to vaccination after two doses of an mRNA vaccine, a proportion of IMID patients show reduced responses compared to healthy controls (7)(8)(9)(10)(11)(12)(13)(14), as confirmed in recent meta-analyses (15,16). In particular, patients receiving glucocorticoids, methotrexate, mycophenolate, anti-TNF and B-cell depleting therapy may have attenuated serological responses to COVID-19 vaccines (7,11,13,15,17,18).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Efeitos adversos foram equivalentes em ambos os grupos e não há relatos de efeitos graves ou de piora no quadro clínico. 5 Em estudo mais recente dos efeitos da vacina em pessoas que foram expostas ao vírus e apresentaram sintomas para COVID-19, foi concluído que apenas uma dose já é suficiente para garantir os níveis ideais de anticorpos. Após a primeira dose, os voluntários que nunca entraram em contato com SARS-CoV-2 possuíram respostas imunológicas inferiores aos outros participantes.…”
Section: Vacinas Desenvolvidas a Partir Do Gene Do Antígeno Da Glicop...unclassified